Teaching Reading Comprehension to The Eleventh Grade Students of SMK Negeri 3 Parepare Through Two Stay Two Stray Technique - Sulastri (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
Reading comprehension is the ability in understand the meaning of the text that is read. When doing a observation at SMK Negeri 3 Parepare, the researcher found that the student’s reading ability is still low. It was caused by the effect of less technique in teaching, for this reason the students confuse how to get specific information from the reading text easily. Then, the researcher hopes through Two Stay Two Stray Technique able to improve the students reading comprehension. Therefore, the objective of this research is to find out whether or not the use of Two Stay Two Stray Technique is able to improve the reading comprehension of the eleventh grade students of SMK Negeri 3 Parepare. This research used quasi-experimental method with two classes pre-test and post-test design. The population was the eleventh grade students of SMK Negeri 3 Parepare. The sample analysis consisted of 40 students from two classes taken from population of the eleventh grade students of SMK Negeri 3 Parepare. The result of the data analysis showed that Two Stay Two Stray Technique can improve the reading comprehension of the eleventh grade students of SMK Negeri 3 Parepare significantly. It was proved by the mean score of the pre-test was (52.00) and the post-test was (74.75). After analyzing the data by using SPSS. 21.0,the probably value in post-test was (0.00) is lower than the significance value (α) = (0.05). those indicated that H1 was accepted and H 0 was rejected. From this data, the researcher can concluded that by applying Two Stay Two Stray Technique to improve reading comprehension of the eleventh grade students of SMK Negeri 3 Parepare.